Isa Al-Masih 'inda Al-Qadiyaniyat: Dirasat Tahliliyat Naqdiyat - Rusnadi, Rusnadi (Hanifiya: Jurnal Studi Agama-Agama, 2019)
This paper aims to conduct a study of Isa al Masih in the view of al-Qadiyaniah. Islam believes that the prophet Isa al-Masih was appointed by Allah to rise from the pursuit of the Jews who wanted to crucify and kill him and then be lowered at the end of time. This belief is opposed by followers of al-Qodiyaniyah, they consider that the belief of Muslims and Christians is a distorted belief. Al-Qodiyaniah believes that Isa al-Masih did not die and was not taken up to heaven. This study is using a library research method with a qualitative approach. Research results show that Jesus was crucified and did not die on the cross, but Isa al-Masih was lowered from the cross and then migrated to Kasymir until his death and was buried there. And as for the purpose of the appointment of Jesus according to Qodiyaniyah is the departure of Jesus to Kasymir after being crucified, and another purpose of the appointment of Jesus is to elevate the degree and praise for Jesus, not appointed his body. as well as the purpose of the fall of Jesus for the second time is the rise of Islam and Mirza Ghulam Ahmad is a person who is trying to revive that religion of Islam. And among al-Qodiyaniyah's beliefs is that Mirza Ghulam Ahmad is as Isa al-Masih and also as Imam al-Mahdi in one body.